EFEKTI METODA PRERADE NA FUNKCIONALNI I MINERALNI SASTAV BRAŠNA INDIJSKOG ORAHA: - - IDE, PATRICK EJIKE; EKETE, Eje Brendan; Uche, Okorie Nelson (Journal on Processing and Energy in Agriculture, 2022)
This research determined the effects of processing methods on the functional and mineral composition of cashew kernel flour. Three varieties of cashew nut were processed to flour using three methods. The result showed that, functional properties of cashew flour processed with hot oil bath, oven-dry and roasting varied significantly at (p>0.05). Foaming capacity (8.00%, 6.00% and 4.00%),emulsification capacity (2.00%, 2.50%, and 4.50%) and foaming stability (1.00%, 2.00%, and 4.00%) were found to be higher in the roasted samples. Water absorption capacity(92.54%, 172.32%, 116.42%) and oil absorption capacity (88.55%, 85.80%, 73.64%) were found to be higher in hot oil bath samples. Swelling capacity(8.21%, 8.35%, 11.00%)and solubility (16.64%, 14.70%, 20.91%) were observed to higher in oven-dried samples. The mineral composition of cashew flour samples processed using hot oil bath, oven-dried and roasting were varied significantly at(p>0.05) across the varieties and processing methods. Phosphorus (0.72%, 0.69% and 0.68%), Ca (0.30% , 0.37%  and 0.39%), Mg (0.23%, 0.26% and 0.25%), K (0.66%, 0.68% and 0.68%), Mn (17.66ppm, 26.30ppm and 24.37ppm), Cu (22.63ppm, 25.04ppm and 24.84ppm), Zn (141.29ppm, 139.45ppm, 141.10ppm) were significant in hot oil bath samples while Na(28.17ppm, 34.75ppm, 44.07ppm)  and iron (131.66ppm, 117.53ppm,42.37ppm)were dominant in oven-dried flour samples. Generally, it was observed that, processing methods adopted significantly influenced minerals and functional properties of cashew kernel flour at (p>0.05).The cashew kernel flour displayed good characteristics of functional and mineral properties. Therefore, the flour can serve as a functional ingredient in the formulation of snack products as an alternative to legumes/wheat flours